Androgen deficiency in women with adrenal insufficiency. Dehydroepiandrosterone. Review - N F Nuralieva; M Yu Yukina; E A Troshina; N M Platonova (IP Berlin A.V., 2018)
It is known that adrenal insufficiency (AI) is a severe life-threatening disease due to the exceptional role of glucocorticoids and mineralocorticoids in the human body. At the same time, according to some reports, the deficit of androgens synthesized by the adrenal cortex (dehydroepiandrosterone - DHEA and dehydroepiandrosterone sulfate - DHEAS) is associated with an increased risk of death, including increased risk of adverse cardiovascular events, development of osteoporosis, diabetes mellitus and malignant neoplasms. The main source of DHEA and DHEAS in females are adrenal glands, so women with hypocorticism have significantly reduced (down to undetectable) levels of these hormones. However, due to lack of a reliable evidence and, accordingly, clinical recommendations, correction of androgen deficiency in patients with AI is usually not performed. The review discusses the accumulated data on the physiological significance of DHEA and DHEAS, their role in the development of various pathological conditions, as well as safety and efficacy of these drugs.